2017
DOI: 10.1007/s40262-017-0559-8
|View full text |Cite
|
Sign up to set email alerts
|

A Population Pharmacokinetic and Pharmacodynamic Analysis of Abemaciclib in a Phase I Clinical Trial in Cancer Patients

Abstract: Background and ObjectivesAbemaciclib, a dual inhibitor of cyclin-dependent kinases 4 and 6, has demonstrated clinical activity in a number of different cancer types. The objectives of this study were to characterize the pharmacokinetics of abemaciclib in cancer patients using population pharmacokinetic (popPK) modeling, and to evaluate target engagement at clinically relevant dose levels.MethodsA phase I study was conducted in cancer patients which incorporated intensive pharmacokinetic sampling after single a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 18 publications
5
50
1
Order By: Relevance
“…Selection of these dose levels was supported by the clinical dose-response relationship for target engagement and the correlation of p-Rb suppression to clinical activity. Drug doses can be scaled up or down depending on clinical evidence of efficacy and/or toxicity [16]. Data from a phase I trial demonstrated that abemaciclib dose adjustments are not required for adult patients of different sex, age, or body weight [16].…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of these dose levels was supported by the clinical dose-response relationship for target engagement and the correlation of p-Rb suppression to clinical activity. Drug doses can be scaled up or down depending on clinical evidence of efficacy and/or toxicity [16]. Data from a phase I trial demonstrated that abemaciclib dose adjustments are not required for adult patients of different sex, age, or body weight [16].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Drug doses can be scaled up or down depending on clinical evidence of efficacy and/or toxicity [16]. Data from a phase I trial demonstrated that abemaciclib dose adjustments are not required for adult patients of different sex, age, or body weight [16]. The absolute bioavailability of abemaciclib after a single oral dose of 200 mg is 45% and the median T max ranges from 4 to 6 h ( Table 1).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Abemaciclib is characterized by an extensive variability in cancer patients, independently from demographics (sex, age, body weight). Data from healthy subjects show that increasing the dose and/or duration of abemaciclib treatment results in a reduction in the fraction of dose absorbed [ 57 ]. Food intake slightly modifies abemaciclib PK profile without relevant clinical consequences; although high fat and high caloric meal increases AUC by 9% and C max by 26%.…”
Section: Introductionmentioning
confidence: 99%
“…Food intake slightly modifies abemaciclib PK profile without relevant clinical consequences; although high fat and high caloric meal increases AUC by 9% and C max by 26%. Overall PK variability of abemaciclib is not meaningfully influenced by food-effect [ 16 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation